2021
DOI: 10.24996/ijs.2021.62.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hindiya Dam on Rotifera Community of Euphrates River on the Northern of Babil Governorate, Iraq

Abstract: This study was the first of its kind on the Hindiya Dam, which is considered one of the important dams in Euphrates River. Five sites were chosen on the north of Babil Governorate in   order to know the rotifers biodiversity features and the impact of the Hindiya Dam on it's during the 2019. Site2(S2) was located near the dam to reflect the rotifers diversity of this site, whereas , S1 was located at the upstream of the dam as a control site, and  S3, S4 and S5 were located down the dam.  Rotifers  showed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As for the spatial changes in the rotifera species richness index values, they were recorded the highest on site 1 which could be due to many aquatic plants. Whereas their decrease in site 3 could be linked to high turbidity or lack of food [39]. The current study concluded that the low flow of the GGDC water helped to increase rotifera assemblage.…”
Section: S1mentioning
confidence: 55%
“…As for the spatial changes in the rotifera species richness index values, they were recorded the highest on site 1 which could be due to many aquatic plants. Whereas their decrease in site 3 could be linked to high turbidity or lack of food [39]. The current study concluded that the low flow of the GGDC water helped to increase rotifera assemblage.…”
Section: S1mentioning
confidence: 55%
“…(3) (2) where: Q Sm < 0.1 -toxicity risk is negligible; 0.1 < Q Sm < 0.5 -the risk is low, but the nonhazardous sediments must be checked; Q Sm > 0.5 -risk is non-negligible, and it is a possible hazard for aquatic life.…”
Section: Sediment Quality Criteriamentioning
confidence: 99%
“…Rotifers have shown dominance in most studies, which is due to their small size, short life cycle, and tolerance to the environmental factors, as well as for the fact that they are opportunistic species that are capable of swallowing microorganisms like bacteria and detritus [11]. Many studies, such as those of Al-Bahathy and Nashaat [12], recorded highest density of rotifers in the Euphrates River near Hindiya Dam during winter. While the study of Salman et al [13] in Al-Gharraf River recorded the highest density during spring and summer.…”
Section: Introductionmentioning
confidence: 99%